Signaling Domains of Mucin Msb2 in Candida albicans - Swidergall, Marc (Eukaryot Cell, 2015)
Candida albicans adapts to the human host by environmental sensing using the Msb2 signal mucin, which regulates fungal morphogenesis and resistance characteristics. Msb2 is anchored within the cytoplasmic membrane by a single transmembrane (TM) region dividing it into a large N-terminal exodomain, which is shed, and a small cytoplasmic domain. Analyses of strains carrying deleted Msb2 variants revealed an exodomain segment required for cleavage, shedding, and all functions of Msb2. Phosphorylation of the mitogen-activated protein kinase (MAP kinase) Cek1 was regulated by three distinct regions in Msb2: in unstressed cells, N-terminal sequences repressed phosphorylation, while its induction under cell wall stress required the cytoplasmic tail (C-tail) and sequences N-terminally flanking the TM region, downstream of the proposed cleavage site. Within the latter Msb2 region, overlapping but not identical sequences were also required for hyphal morphogenesis, basal resistance to antifungals, and, in unstressed cells, downregulation of the PMT1 transcript, encoding protein O-mannosyltransferase-1. Deletion of two-thirds of the exodomain generated a truncated Msb2 variant with a striking ability to induce hyperfilamentous growth, which depended on the presence of the Msb2-interacting protein Sho1, the MAP kinase Cek1, and the Efg1 transcription factor. Under cell wall stress, the cytoplasmic tail relocalized partially to the nucleus and contributed to regulation of 117 genes, as revealed by transcriptomic analyses. Genes regulated by the C-tail contained binding sites for the Ace2 and Azf1 transcription factors and included the ALS cell wall genes. We concluded that Msb2 fulfills its numerous functions by employing functional domains that are distributed over its entire length.